SOME COST ACCOUNTING CONCEPTS OF WIDER APPLICATION. - Noble, H. S. (The Accounting Review, 1926)
Abstract The second decade of the present century was marked by a great development in that phase of accounting having to do primarily with principles, practices, and procedures in the field of manufacturing. The name applied to this body of material was "cost accounting." During this period, the development of cost systems in manufacturing institutions, the attention of engineers and industrial associations to cost accounting, and the inclusion of courses in cost accounting in the larger universities of the country gave evidence of this new development in the field of accounting. Frequent statements of writers that the principles of cost accounting might advantageously be applied to selling and administrative expenses, and that commercial enterprises might well emulate the cost accounting of industrial concerns, are conducive to serious reflection upon the possible existence of a science, inherent in factory or cost accounting, which is more fundamental than surface conditions seem to indicate. There is at least a suggestion that the description of technical devices and procedures which forms the bulk of cost accounting does not exhaust the possibilities of the subject.